“SERBS OF MOSAIC FAITH”: AN ANALYSIS OF DAVID A. KOEN’S “ORATIONS” AS A MODEL FOR NATIONAL INTEGRATION OF JEWS - Tucakov, Nikola (Srpska politička misao, 2026)
This article presents an analysis of the formation and discursive structure of texts collected in the book Orations Dedicated to the Serb Youth of Mosaic Faith, as a reflection of a particular project of integration of the Jewish population into the framework of the Serbian nation towards the end of the 19th century. Based on the theoretical foundations of Rogers Brubaker and Siniša Malešević, the key ideological elements of such a project are identified, which allows for gaining insights both about the scope of conceptualising nationality immediately following the formation of a nation-state in the Balkans and the ways in which representatives of minority groups could present themselves as potential participants in shaping such conceptions. Following a contextualist approach, the analysis aims at uncovering a “political language”, one significantly informed by particular socio-political relations on the basis of which it may be (and may have been) possible to understand the nation and nationhood at a particular time and place.
Keywords: Jewish integration; national integration; Serbs of Mosaic faith; David A. Koen; Serbian nationalism; political languages